ANALYSIS OF EFFECT OF SPEED SPEED AND PHYSICAL EXPERIENCE ON PAINTING TEMPERATURE ON LATHE MACHINE - Didik Nurhadiyanto (Jurnal Penelitian Saintek, 2002)
The propose  of this experiment was to analyze the effect of feedingspeed and cutting depth that effecting cutter temperature. The scatter diagram and variant analysis was used to analyze the data of thisexperiment. The analysis shows that both feeding  speed and cutting depth were influencing cutter temperature. The effect of interaction between feeding  speed  and  cutting  depth  were  influencing  cutter temperature.